Security Challenges of Nepal: Perspective from National Security Policy-2016 - Baral, Bhim Nath (INTELLIGENCE Journal of Multidisciplinary Research, 2026)
Nepal has always remained cautious in its security since the very beginning of nation building. A sensitive geostrategic location and internal political dynamism have consistently remained pivotal in shaping its national security. Even today, the country has been facing numerous traditional and non-traditional security challenges. Hence, the article aims to analyze the security challenges of Nepal in the light of ‘National Security Policy- 2016’. The policy seems to be a guideline for fostering the state’s capacity to preserve sovereignty, integrity, independence, and the overall dignity of the state in the comity of nations. The article adopts a qualitative document analysis method gathered from secondary sources. The security issue has become more crucial mainly because of geopolitical position and the growing influence of global power shift. Further, there has been a gradual shift in the traditional notion of security, focusing on human-centric elements. Hence, the policy states that political instability, economic dependency, governance problems, erosion of state’s capacity to maintain laws and order, growing danger of natural calamities, degrading environment, and the rise of extremist tendencies are the primary sources of challenges to national security. All these fragilities in internal security has led to an increasing external security threat. The study shows that Nepal needs to strengthen its institutional capacity and capitalize resilience policy consideration to maintain security intact. Thus, the study receives theoretical insights from political Realism, Liberalism, and Wales and English school of international relations, Critical, and small power approaches.